2014
DOI: 10.1111/ijsa.12062
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Mobile Devices in High‐stakes Remotely Delivered Assessments and Testing

Abstract: With Internet access no longer restricted to desktop and laptop computers, job applicants now have the opportunity to complete remotely delivered assessments on mobile, handheld small screen devices such as smartphones, and personal digital assistants. In this study, a large dataset is used to investigate demographic and score differences between job applicants who completed a remotely delivered high-stakes assessment on a mobile device and those who completed it on a nonmobile device. Based on a sample of 3,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
65
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 31 publications
6
65
2
1
Order By: Relevance
“…This is an important difference since prior research has shown that the user interface can have an impact on computer and web-based test scores (Bridgeman, Lennon, & Jackenthal, 2003;Huff, Cline, & Guynes, 2012;Květon, Jelínek, Vobořil, & Klimusová, 2007;Schroeders and Wilhelm, 2010;Wästlund et al's, 2008). More specifically to this research, very recent research have found differences in mean test scores between mobile devices and traditional computers (Arthur et al, 2014;Illingworth et al, 2014;Morelli et al, 2014;Sanchez & Branaghan, 2011;Sanchez & Goolsbee, 2010). However, the effect sizes of those differences have traditionally been small and very little is known as to why the differences exist at all.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…This is an important difference since prior research has shown that the user interface can have an impact on computer and web-based test scores (Bridgeman, Lennon, & Jackenthal, 2003;Huff, Cline, & Guynes, 2012;Květon, Jelínek, Vobořil, & Klimusová, 2007;Schroeders and Wilhelm, 2010;Wästlund et al's, 2008). More specifically to this research, very recent research have found differences in mean test scores between mobile devices and traditional computers (Arthur et al, 2014;Illingworth et al, 2014;Morelli et al, 2014;Sanchez & Branaghan, 2011;Sanchez & Goolsbee, 2010). However, the effect sizes of those differences have traditionally been small and very little is known as to why the differences exist at all.…”
Section: Introductionmentioning
confidence: 91%
“…What research that does exists (Arthur, Doverspike, Muñoz, Taylor, & Carr, 2014;Illingworth, Morelli, Scott, & Boyd, 2014;Morelli, Mahan, & Illingworth, 2014;Sanchez & Branaghan, 2011;Sanchez & Goolsbee, 2010) demonstrates that assessments can be impacted by the type of device that was used to completed it and that this impact is not necessarily consistent across different types of assessments. What little we know about the differences that exist is limited by the lack of experiments investigating issues that may cause differences on assessments across devices.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations